Investigation into the effects of feeding schedule on body condition, aggressiveness, and reproductive failure in group housed sows - Schneider, J.D.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; DeRouchey, Joel M.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 208 sows and 288 gilts (PIC Line C29) were used to determine the influence of feeding frequency (2 versus 6 times per day) in gestation on performance and welfare measurements. The experiment was conducted on a commercial sow farm in northeast Kansas that typically housed gestating sows and gilts in pens. Treatments consisted of feeding similar amounts of feed to each sow or gilt over 2 (07:00 and 15:30) or 6 meals per day (07:00, 07:30, 08:00, 15:30, 16:00, and 16:30 hours). There were 8 sows or 12 gilts in each pen. Gilts and sows were moved to pens after breeding. In gestating sows, there were no differences (P>0.10) between treatments in ADG, backfat change, or variation in body weight. There was a trend (P<0.08) for sows fed twice a day to farrow more total number born, but number born alive or other measures of reproductive performance were not different (P>0.10) among treatments. Sows fed 6 times a day had increased vocalization during the morning (P<0.07) and afternoon (P<0.01) feeding periods, compared with sows fed twice a day, but sows fed twice a day had more skin (P<0.01) and vulva (P<0.04) lesions, as well as a small, but significant, increase in feet/leg (P<0.01) and hoof (P<0.02) problems. In this commercial facility, the standard management protocol required moving gilts to a different gestation facility. On d 42, two pens of gilts with similar breeding dates and treatment were combined and moved to another facility with larger pens until farrowing. From d 0 to 42, gilts fed 6 times a day had greater ADG (P<0.07) and d-42 backfat (P<0.09). After movement to the larger groups from d 42 to farrowing, ADG was similar (P > 0.10) for gilts fed 2 or 6 times per day. Gilts fed twice a day had less weight variation at both d 42 (P<0.04) and at farrowing (P<0.10). In gilts, there were no differences (P>0.10) for reproductive performance, skin and vulva lesions, and leg/feet and hoof scores. In conclusion, there were few growth, farrowing, or aggression differences among gilts fed either 2 or 6 times per day. This suggests that either feeding method is suitable for group-housed gilts. Among sows, different feeding frequency resulted in few growth or farrowing-performance differences. Feeding 6 times per day did result in a small, but significant, reduction in skin and vulva lesions and structural-problem scores, while increasing vocalization. Increasing the feeding frequency from 2 to 6 times per day does not seem to have a dramatic negative or positive impact on performance or welfare of group-housed gilts and sows.
Keywords: Feeding frequency gilts; Group housing; Gestation; Sows; Swine